2017
DOI: 10.1063/1.5007655
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetoelectric coupling in a composite multiferroic system via interposing a thin film polymer

Abstract: Enhancing the magnetoelectric coupling in a strain-mediated multiferroic composite structure plays a vital role in controlling magnetism by electric fields. An enhancement of magnetoelastic coupling between ferroelectric single crystal (011)-cut [Pb(Mg1/3Nb2/3)O3](1-x)-[PbTiO3]x (PMN-PT, x≈ 0.30) and ferromagnetic polycrystalline Ni thin film through an interposed benzocyclobutene polymer thin film is reported. A nearly twofold increase in sensitivity of remanent magnetization in the Ni thin film to an applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…A number of mechanisms for controlling magnetism using electric fields have been utilized. One approach has been to use multiferroic (MF) materials in which the magnetic moments are either directly coupled to electric dipoles (intrinsic multiferroics) or strain-coupled to piezoelectric materials in composite heterostructures 612 . There are very few intrinsic MF materials at room temperature, thus composite MF materials are more commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…A number of mechanisms for controlling magnetism using electric fields have been utilized. One approach has been to use multiferroic (MF) materials in which the magnetic moments are either directly coupled to electric dipoles (intrinsic multiferroics) or strain-coupled to piezoelectric materials in composite heterostructures 612 . There are very few intrinsic MF materials at room temperature, thus composite MF materials are more commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…While useful in a wide range of other applications, composite MFs have remained unsuitable for spintronic devices because of issues such as clamping with the substrate (which strongly limits the generated strain) or mechanical fatigue. 4 , 5 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a small edge roughness is confirmed by scanning electron microscopy imaging (see Figure S4 in Supporting Information). Interestingly, a recent study has shown that interface defects introduced by the PMN–PT surface roughness can be reduced by depositing a thin film polymer between the PMN–PT and Pt layers, offering a possible path toward a pinning-free multiferroic system with a more uniform magnetic response.…”
mentioning
confidence: 99%